2020
DOI: 10.1038/s41598-020-66128-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori patient isolates from South Africa and Nigeria differ in virulence factor pathogenicity profile and associated gastric disease outcome

Abstract: Helicobacter pylori is a gram-negative, spiral-shaped bacterial pathogen and the causative agent for gastritis, peptic ulcer disease and classified as a WHO class I carcinogen. While the prevalence of H. pylori infections in Africa is among the highest in the world, the incidence of gastric cancer is comparably low. Little is known about other symptoms related to the H. pylori infection in Africa and the association with certain phenotypes of bacterial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
0
16
2
Order By: Relevance
“…The occurrence factors of peptic ulcer are complex, including HP infection, excessive gastric acid secretion, infection, systemic diseases, poor diet and living habits, emotional stress, heredity, etc. [17][18][19] When the local inflammatory response of patients is prolonged, the inflammatory response of TNF-a will be enhanced, and even the local inflammatory response will be enhanced. Therefore, the serum levels of IL-6 and TNF-a are closely related to the changes of peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence factors of peptic ulcer are complex, including HP infection, excessive gastric acid secretion, infection, systemic diseases, poor diet and living habits, emotional stress, heredity, etc. [17][18][19] When the local inflammatory response of patients is prolonged, the inflammatory response of TNF-a will be enhanced, and even the local inflammatory response will be enhanced. Therefore, the serum levels of IL-6 and TNF-a are closely related to the changes of peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in one patient, H. pylori was detected in corpus biopsy but absent in the antrum. Palamides et al [ 15 ] reported similar findings in which H. pylori was detected in biopsies from either antrum or corpus of some patients using conventional PCR. This suggest that there are variations in the distribution of H. pylori in the gut of H. pylori infected patients.…”
Section: Discussionmentioning
confidence: 68%
“…The expression of a specific virulence factor facilitates the interplay between the host and the bacterium [ 39 ]. A recent study by Palamides et al [ 40 ] shows that H. pylori isolates differ in virulence factor and disease outcome. So far, the eradication of H. pylori has become increasingly challenging.…”
Section: Introductionmentioning
confidence: 99%